2009
DOI: 10.1080/03235400601069563
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of disease resistance againstXanthomonas campestrispv.moriin mulberry (Morusspp.) and identification of germplasm with high resistance

Abstract: Genetic analysis of disease resistance against Xanthomonas campestris pv. mori in mulberry (Morus spp.) and identification of germplasm with high resistance, Archives Of Phytopathology And Plant Protection, 42:3, 291-297, AbstractScreening of 82 mulberry germplasms under field conditions against bacterial leaf spot (BLS) caused by Xanthomonas campestris pv. mori exhibited considerable variability for BLS resistance ratings amongst the genotypes. Nearly immune reaction to BLS was observed in Rotundiloba followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
(7 reference statements)
2
6
0
Order By: Relevance
“…The obtained DSI values confirm our previous findings of resistance and susceptibility in these lines (Banerjee et al 2009). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The obtained DSI values confirm our previous findings of resistance and susceptibility in these lines (Banerjee et al 2009). …”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, the sources of BLS resistance have been identified under field condition (Banerjee et al 2009), but mulberry resistance to BLS is polygenic and quantitatively inherited (Banerjee et al 2012). This coupled with high heterozygous plant behaviour and sex-incompatibility are the major impediments for targeted BLS improvement in mulberry.…”
Section: Introductionmentioning
confidence: 98%
“…Screening of mulberry germplasm using pathogenic L. theobromae isolates, and identification of highly durable BRR resistant varieties can aid in achieving sustainable sericulture. Mulberry researchers in India have identified resistant accessions to bacterial leaf spot (Xanthomonas campestris), powdery mildew (Phyllactinia corylea), charcoal root rot (M. phaseolina), and root knot (Arunakumar et al, 2021;Banerjee et al, 2009;Chattopadhyay et al, 2010;Maji, 2011;Pinto et al, 2018). To our knowledge, there is no report on screening of germplasm resistance against L. theobromae causing BRR.…”
Section: Discussionmentioning
confidence: 99%
“…It was diagnosed as plant bacterial disease and found that a majority of the wilt plants surveyed were not caused by R. solanacearum. Eight bacterial diseases of mulberry have been reported to be caused by different species in six genuses (Erwinia, Ralstonia, Pseudomonas, Phytoplasm, Xanthomonas and Xylella) [8][9][10]. However, no mulberry bacterial disease associated with Enterobacter was reported so far.…”
mentioning
confidence: 99%